Investigations of ductile damage during the process chains of toothed functional components manufactured by sheet-bulk metal forming - Isik, Kerim; Gerstein, Gregory; Schneider, Thomas; Schulte, Robert Karl; Rosenbusch, Daniel; Clausmeyer, Till; Nuernberger, Florian; Vucetic, Milan; Koch, Sergej; Huebner, Sven; Behrens, Bernd-Arno; Tekkaya, A. Erman; et al. (Production Engineering, 2016)
Sheet-bulk metal forming processes combine conventional sheet forming processes with bulk forming of sheet semi-finished parts. In these processes the sheets undergo complex forming histories. Due to in- and out-of-plane material flow and large accumulated plastic strains, the conventional failure prediction methods for sheet metal forming such as forming limit curve fall short. As a remedy, damage models can be applied to model damage evolution during those processes. In this study, damage evolution during the production of two different toothed components from DC04 steel is investigated. In both setups, a deep drawn cup is upset to form a circumferential gearing. However, the two final products have different dimensions and forming histories. Due to combined deep drawing and upsetting processes, the material flow on the cup walls is three-dimensional and non-proportional. In this study, the numerical and experimental investigations for those parts are presented and compared. Damage evolution in the process chains is simulated with a Lemaitre damage criterion. Microstructural analysis by scanning electron microscopy is performed in the regions with high mechanical loading. It is observed that the evolution of voids in terms of void volume fraction is strongly dependent on the deformation path. The comparison of simulation results with microstructural data shows that the void volume fraction decreases in the upsetting stage after an initial increase in the drawing stage. Moreover, the concurrent numerical and microstructural analysis provides evidence that the void volume fraction decreases during compression in sheet-bulk metal forming.
LFT Import::2019-07-29 (2147)
Keywords: FE simulation; Lemaitre damage model; Sheet-bulk metal forming